JUSTICE, HUMAN RIGHTS, AND LEGAL REFORM: A PROGRESSIVE CRIMINAL JUSTICE MODEL FOR BANGLADESH (Isagoge - Journal of Humanities and Social Sciences, 2025)
This research provides a methodological and theoretical analysis of the structural barriers to Bangladesh’s criminal justice system, describing it as a culturally embedded scholarly problem influenced by colonial histories, procedural injustice, and institutional human rights violations. The study critically investigates how justice is undermined on an ongoing basis in contravention of constitutional safeguards and international human rights responsibilities. It proposes a progressive, rights-based criminal justice paradigm for Bangladesh, combining restorative justice philosophy with democratic law change. This work contributes to a paradigm shift toward inclusive justice rather than retributive justice by encouraging an inventive confluence of legal theory and reform practice. The research, which focuses on national shortfalls but is guided by international human rights standards, provides a widely repeatable method for assessing legal change in the context of justice and human rights. The findings are particularly valuable for academics, politicians, and practitioners working to establish of decolonized and transitional justice frameworks.
Keywords: Bangladesh; Criminal Justice Reform; Human Rights; Restorative Justice; Social Democracy